Improvements In The Strategic Use Of The Marketing Matrices Applying Dynamics Parameters Based On Time: A Better Analysis Of Prospect - Navarra, Daniela; Scaini, Luca (European Scientific Journal, ESJ, 2016)
Matrices are among the main analytical tools used in marketing. The present paper focuses on the possibility to make them consistently explorative of a business prospect, not just in a mechanical way but in a logical and quantitatively probabilistic way. Matrices, being static, appear in contrast with the real meaning of marketing itself (being a verb it is an action). Actually, lack of the matrices is that they do not consider the temporal evolution and offer a very simple and static frame and indeed a snapshot of the business environment. The purpose of the present paper is to understand â€œto what extent the matrices can be improved to perform dynamic prospective analyses, thanks to specific improvementsâ€: - Complex variables - Cartesian plan and derived curves - Use of the chronotropic quadric-dimensionality through spacetime factor influencing the mechanical results It is considered only the case of the four cells based matrix (and experimentation is pursued via the Ansoffâ€™s one), leaving the nine-cell based matrices to the field of actual limitations and future improvements. The standard format can be implemented by the adoption of new format and complex variables, which are holistic, and through the utilization of a temporal ratio, to show the temporal dynamism and make them suitable for prospective analysis and become a tool of management of the companyâ€™s evolution.